Review: Characterization and Modeling of the Mechanical Properties of Lithium-Ion Batteries - Kermani, Golriz; Sahraei, Elham (Energies (Basel), 2017)
Li-ion batteries have become a dominant power source in consumer electronics and vehicular applications. The mobile use of batteries subjects them to various mechanical loads. The mechanisms that follow a mechanical deformation and lead to damage and failure in Li-ion batteries have only been studied in recent years. This paper is a comprehensive review of advancements in experimental and computational techniques for characterization of Li-ion batteries under mechanical abuse loading scenarios. A number of recent studies have used experimental methods to characterize deformation and failure of batteries and their components under various tensile and compressive loading conditions. Several authors have used the test data to propose material laws and develop finite element (FE) models. Then the models have been validated against tests at different levels from comparison of shapes to predicting failure and onset of short circuit. In the current review main aspects of each study have been discussed and their approach in mechanical testing, material characterization, FE modeling, and validation is analyzed. The main focus of this review is on mechanical properties at the level of a single battery.